De-embedding of Reverse Recovery Losses in Fast Switching VRM Applications - Dürbaum, Thomas; et al. (18th Annual Applied Power Electronics Conference, APEC 2003, 2003)
For the Synchronous Buck converter used in VRM applications, one major contributor to switching losses is reverse recovery. These losses however cannot directly be measured because capacitive current and several other phenomena superimpose the mere reverse recovery. The paper describes how calculate the capacitive part of the drain current and how to deembed the channel current out of the total drain current. This can show the size of Qrr and reveal effects such as gate bouncing and avalanche breakdown.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.lselek.deembe
Keywords: Capacitive current; De-embedding; Gate bouncing; Half-bridge; MOSFET characterisation; Reverse recovery; Switching behaviour; Synchronous rectification; VRM